Comparative primate socioecology - Lee, Phyllis C. (Cambridge studies in biological anthropology, 1999)
Comparative Primate Socioecology is an exciting new book drawing together recent and controversial findings from field research on a wide variety of primate species including lemurs and humans. It creates a new synthesis and provides methodologies for all those interested in human and non-human primate behaviour and evolution.